Risk and protective factors influencing sexual orientation among Islamic boarding school students in Jember, Indonesia - Mubarok, Ibnu; Rif'ah, Erwin Nur; Rokhmah, Dewi (Faculty of Medicine, Universitas Islam Indonesia, 2025)
Background: The sexual orientation of students is influenced by various factors. Islamic boarding school is one of the places where risky sexual orientation can occur among students. This behaviour must be addressed so that it does not cause more severe health impacts.Objective: This study aims to explore the risk and protective factors of sexual orientation from the experiences of students at Islamic Boarding School in Jember Indonesia. Methods: This study was a qualitative study with a phenomenological approach. There were 16 informants consisting of key informants, main informants, and additional informants. The research informants were selected using the snowball sampling techniques. In-depth interviews were conducted to study the risk and protective factors of sexual orientation among Islamic Boarding School students in Jember, Indonesia. Data were analysed using thematic content analysis. Results: The study showed that, in terms of risk factors, all informants had been victims of bullying because of a negative social, which made the informants feel depressed. All informants experienced mental trauma due to stigma and discrimination which caused the informants to feel depressed. The presence of protective factors was considered beneficial for individuals because this condition transformed negative emotional perceptions into positive perceptions, thereby strengthening personal development and resilience. The influence of religion and internal factors have a strong influence on making individuals have heterosexual desires and helping them recover from the bad effects experienced during periods of homosexual behaviour. Conclusion: Factors that influence students’ sexual orientation towards homosexuality include discrimination, weak individual resilience, and oppression. Based on this, assistance is needed to help students with homosexual orientation maintain a stable condition.